Islamic Theology and Pluralism: Aqidah in Multicultural Contexts - Fiqi Restu Subekti; Achmad Hidayatullah; Noni Kensiwi (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Pluralism has become an unavoidable reality in contemporary multicultural societies, raising important theological questions regarding how Islamic belief (aqidah) engages religious diversity without losing doctrinal coherence. In contexts such as Indonesia, where social life is shaped by deep religious plurality, Islamic theology is increasingly challenged to articulate faith as a source of ethical guidance, social harmony, and civic responsibility. This study aims to analyze the role of aqidah in responding to pluralism through theological discourse, Islamic education, and social practice. The research employs a qualitative normative interpretative method based on systematic literature analysis of contemporary Islamic theological, educational, and legal studies related to pluralism and religious moderation. Data are examined through thematic and comparative analysis to identify patterns of theological reasoning and practical application. The findings show that aqidah functions as a dynamic moral foundation that sustains firm belief while promoting moderation, dialogue, and coexistence. When integrated into education and da’wah, aqidah strengthens social cohesion and ethical engagement in multicultural settings.